High hydrostatic pressure effects investigated by neutron scattering on lipid multilamellar vesicles - Trapp, Marcus; Marion, Jérémie; Tehei, Moeava; Demé, Bruno; Gutberlet, Thomas; Peters, Judith (Physical chemistry, chemical physics, 2013)
The effects of high hydrostatic pressure on the structure and dynamics of model membrane systems were investigated using neutron scattering. Diffraction experiments show shifts of the pre- and main-phase transitions of multilamellar vesicles of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) to higher temperatures with increased pressure which are close to results observed previously by other techniques, namely (10.4 ± 1.0) K kbar−1 and (20.0 ± 0.5) K kbar−1 for the two transitions. Backscattering spectroscopy reveals that the mean square displacements in the liquid phase are about 10% smaller at 300 bar and about 20% smaller at 600 bar compared to atmospheric pressure, whereas in the gel phase below the main phase transition the mean square displacements show a smaller difference in the dynamics of the three pressure values within the studied pressure range.
Gesehen am 10.02.2022